First Trimester Serum Analytes, Maternal Characteristics and Ultrasound Markers to Predict Pregnancies at Risk for Preterm Birth - Stout, Molly J. (2012)
INTRODUCTION: Markers of placental dysfunction are used for risk prediction of adverse obstetric outcomes including preeclampsia and growth restriction. Although medically indicated preterm birth is often distinguished from spontaneous preterm birth, we hypothesize that similar placental dysfunction may underlay all preterm birth. We aimed to investigate whether first trimester placental protein 13 (PP-13), pregnancy associated plasma protein A (PAPP-A) and uterine artery pulsatility index, with maternal characteristics could be used to predict all preterm birth. METHODS: Prospective cohort study of singleton gestations between 11-14 weeks who underwent serum measurement of PP-13, PAPP-A, and measurement of uterine artery Doppler pulsatility index. Primary outcomes were preterm birth (PTB) at less than 37 and 33 weeks. Analysis performed both including and excluding preeclampsia to assess the utility of the predictors for all types of preterm birth. Predictive models assembled using logistic regression with each predictor alone and in combination, along with maternal characteristics. Predictive utility of models was assessed using receiver operating curve (ROC) analysis and sensitivities for fixed-false positive values. RESULTS: Of 471 women, PTB occurred in 12.5% and early PTB (<33 weeks) occurred in 4.7%. PP13 was decreased in PTB <37 weeks. PAPP-A was decreased in a dose-response pattern for PTB at <37 weeks and <33 weeks. Uterine artery pulsatility index was increased in early PTB. All patterns of predictors remained the same whether patients with preeclampsia were excluded or included suggesting predictive utility for all causes of PTB. Predictive models all demonstrated good predictive ability with ROC ≥ 0.90. CONCLUSIONS: PP-13, PAPP-A, and uterine artery Doppler pulsatility index obtained in the first trimester are good predictors of all types of preterm birth, both indicated and spontaneous. Models including first trimester markers combined with maternal characteristics demonstrated good predictive ability and could be investigated for application of targeted prophylactic strategies.